Dual-energy computed tomography collagen density mapping of the cranio-cervical ligaments: a retrospective feasibility study - Wittig, Thomas Matthias; Ziegeler, Katharina; Kreutzinger, Virginie; Golchev, Milen; Ponsel, Simon; Diekhoff, Torsten; Ulas, Sevtap Tugce (Diagnostics, 2022)
The objectives of this study were to investigate the mean collagen content of the atlanto-axial joint (AAJ) ligaments in a cohort without inflammatory disease and to analyze clinical confounders such as age, sex, and presence of ligamentous calcifications. A total of 153 patients who underwent dual-energy computed tomography (DECT) due to various reasons (e.g., suspected cancer or infection) were included in this retrospective study. Reconstruction of collagen density maps from the DECT dataset was performed. Region of interest (ROI) analysis was performed to assess densities in the following regions: ligamentum transversum atlantis (LTA), ligamenta alaria, fasciculi longitudinales, ligamentum nuchae, and retro-odontoid soft tissue (RDS). Osteoarthritis (OA) and the presence of calcifications were assessed by two experienced readers blinded to clinical data. Subgroup comparisons were performed using unpaired t-tests. The correlation of collagen density and clinical factors was investigated using Pearson’s correlation coefficient. Mean LTA collagen density was 141.7 (SD 35.7). Ligamentous calcifications were rare (14.4 %). OA of the AAJ was common (91.5 %). LTA collagen density was not associated with age (Pearson’s r of 0.109; p = 0.180) and was not significantly higher in patients with OA (p = 0.070). No correlations between RDS thickness, collagen density or calcifications were found. Our results show collagen density mapping of the cranio-cervical joint ligaments to be feasible; collagen densities are not significantly associated with age, sex, AAJ degeneration, or asymptomatic ligamentous calcification.
Gesehen am 12.12.2024